Effect of Microfinance Banks on the Growth of Selected Small and Medium Scale Enterprises in Makurdi Metropolis, Benue State - Garba, Adamu (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2019)
This study examined the effect of microfinance banks on the growth of selected small and medium scale enterprises in Makurdi Metropolis, Benue State.The study was anchored on Pecking Order theory. The researcher used both primary and secondary sources from a population of 960 and a sample of 282 respondents obtained by the use of a structured questionnaire. The data collected were analyzed using descriptive statistics such as frequency, simple percentage and the relationship between the variables of the model was tested using multiple linear regression analysis. The result of the regression analysis indicates that a positive relationship exist between Credit by Microfinance (CMF) Job Creation (JOC) of selected SMEs in Makurdi Metropolis and the relationship is statistically significant (p<0.05). A positive relationship exist between Credit by Microfinance and Business Expansion (BEX) of selected SMEs in Makurdi Metropolis and the relationship is statistically significant (p<0.05). A negative relationship exist between Savings Mobilization and the Growth of Small and Job Creation (JOC) of selected SMEs in Makurdi Metropolis and the relationship is not statistically significant (p>0.05). A positive relationship exist between Savings Mobilization (SMB) and Business Expansion (BEX) of selected SMEs in Makurdi Metropolis and the relationship is statistically significant (p<0.05). It was concluded that micro finance does enhance the job creation and expansion capacity of small business in Nigeria. It was recommended among others that microfinance bank should adopt similar strategies adopted by deposit money banks in deposit mobilization because it is by so doing that they will be able to grant quality loans to entrepreneurs which will lead to job creation in the economy.